Apocalypse Now? Kritische Diskursanalyse der Berichterstattung der BILD-Zeitung vom 12.09.01 bis zum 7.11.01 - Bünger, Iris (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
The role played by the media in the construction of societal reality is both – determined by discourse and determines discourse. The media can be regarded as a kind of „magnifying glass” that collects information and focuses it for the masses. The reporting of the BILD-Zeitung, a leading figure in mass print media is analysed after the attacks on US-targets on September 11, 2001. The discursive strategy to define terror as war and to prepare the military counter attacks entailing „unlimited German Solidarity” is demonstrated by illumination of the argumentation strategies and collective symbolism.